PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA KANTOR INSPEKTORAT KABUPATEN SIJUNJUNG - Eva Suryany; Daniel Jusari; Osmidar Osmidar (Jurnal Public Administration, Business and Rural Development Planning, 2023)
The purpose of this research is to find out how the leadership is at the Sijunjung Regency Inspectorate office and to find out how the employee performance is at the Sijunjung Regency Inspectorate office and to find out how leadership influences employee performance at the Sijunjung Regency Inspectorate office. The method used in this study is quantitative using survey methods, namely research that takes samples from one population and uses a questionnaire. The results of this research are that the leadership of an inspector at the Sijunjung District Inspectorate office is still not running optimally as expected, this can be seen from the presence of employees who come and go home not on time, the lack of ability of superiors to control employees and the superiors are not strict in giving rewards or punishmen to employees resulting in reduced performance and employee performance at the Sijunjung District Inspectorate Office has not run as it should, this is because there are still jobs that are not completed on time, work results that are not in accordance with targets, repeated mistakes so that there is often a waste of costs, labor and money, as well as the lack of a sense of responsibility for employees at work and the influence of this leadership indicates a positive influence generated by leadership on performance